Evaluating gas turbine fouling degradation and impact of washing on engine performance. - Lewis, Andy (Cranfield University, 2017)
Fouling of the compressor of a gas turbine is one of the major contributors to its performance degradation, not only in terms of a reduction in the potential power output revenue and increased fuel costs but also raising the operating temperatures to levels that will have an impact on the servicing intervals and costs. In view of the current economic climate and with the ever-increasing pressure on governments to reduce emissions that contribute to global warming, the need to operate power generating gas turbines in the most efficient way possible is becoming more important. The aim of this study is to demonstrate that using a single compressor dual high-pressure washing system, on multiple gas turbines and a combination of a strict on-line compressor washing regime it is possible not only reduce the rate of compressor degradation, that will enable the period between off-line washes to be extended but also maintain a higher rate of power output throughout this period. Additional benefits will include better fuel efficiency which will lead to a lowering of emissions and the added flexibility of the overall plant operation by reducing the service interventions and shutdowns for off-line washes to the minimum. This study utilises the readily available data from the gas turbine control system to understand how the performance is affected by compressor fouling over time. Once corrected to remove the variations caused by changes in the ambient conditions, the performance trend of the data can be examined in 2 ways. The comparison of the recorded degradation against the gas turbine’s own historic figures and secondly against the relative performances of adjacent machines over similar time periods. The data gathered, from 4 gas turbines, over the 3 years 8 months recording period, provided the opportunity to select 'like for like' starting points in the various life cycles. This enabled direct comparisons of the results, between the various gas turbines that had operated with different compressor washing regimes. These comparisons demonstrated that maintaining an effective on-line compressor washing regime allows for greater potential revenue from exported power; whilst at the same time being more fuel efficient and lowering operating temperatures.
Keywords: Heat rate; base-load; on-line wash frequency; operating hours; productive hours